Polyinosinic‐polycytidylic acid accelerates intestinal stem cell proliferation via modulating Myc expression. Issue 4 (26th September 2019) - Zeng, Huihong; Tang, Jiahui; Yue, Mengzhen; Cheng, Jiaoqi; Fan, Ying; Li, Manjun; Zhang, Xinxin; Li, Huan; Duan, Hongyi; Zhang, Minqing; Fan, Guangqin; Zhu, Qingxian; et al.
Abstract: It is well known that exposure of double‐stranded RNA (dsRNA) to intestine immediately induces villus damage with severe diarrhea, which is mediated by toll‐like receptor 3 signaling activation. However, the role of intestinal stem cells (ISCs) remains obscure during the pathology. In the present study, polyinosinic‐polycytidylic acid (poly[I:C]), mimicking viral dsRNA, was used to establish intestinal damage model. Mice were acutely and chronically exposed to poly(I:C), and ISCs in jejunum were analyzed. The results showed that the height of villus was shorter 48 hr after acute poly(I:C) exposure compared with that of controls, while chronic poly(I:C) treatment increased both villus height and crypt depth in jejunum compared with control animals. The numbers of ISCs in jejunum were significantly increased after acute and chronic poly(I:C) exposure. Poly (I:C)‐stimulated ISCs have stronger capacities to differentiate into intestine endocrine cells. Mechanistically, poly(I:C) treatment increased expression of Stat1 and Axin2 in the intestinal crypt, which was along with increased expression of Myc, Bcl2, and ISC proliferation. These findings suggest that dsRNA exposure could induce ISC proliferation to ameliorate dsRNA‐induced intestinal injury. Abstract : We demonstrated that polyinosinic‐polycytidylic acid (poly[I:C]) induced intestinal stem cell proliferation to ameliorate it acute negative effects on intestinal villi. The positive effects of poly(I:C) on intestine might be involved in increasing expression of cell cycle‐ and apoptosis‐related genes, such as Myc, Bcl2, and so forth.